2017
DOI: 10.1016/j.colsurfb.2016.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan nanoparticles as carrier systems for the plant growth hormone gibberellic acid

Abstract: This work concerns the development of nanocarriers composed of alginate/chitosan (ALG/CS) and chitosan/tripolyphosphate (CS/TPP) for the plant growth regulator gibberellic acid (GA). ALG/CS nanoparticles with and without GA presented mean size of 450±10nm, polydispersity index (PDI) of 0.3, zeta potential of -29±0.5mV, concentrations of 1.52×10 and 1.92×10 nanoparticles mL, respectively, and 100% encapsulation efficiency. CS/TPP nanoparticles with and without GA presented mean size of 195±1nm, PDI of 0.3, zeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(103 citation statements)
references
References 65 publications
5
93
0
5
Order By: Relevance
“…Although not tested separately in the present study, it is known that the CS polymer is nontoxic and for this reason has considerable potential for applications in agriculture, where it can act as a biostimulant and/or reduce abiotic stress in plants, as well as increase resistance against pathogens (Pichyangkura and Chadchawan, 2015). According to this, in recent studies of our group, different CS-based nanoparticles have been shown to not impair germination and initial growth of Phaseolus vulgaris (Pereira et al, 2017a(Pereira et al, , 2017b. Regarding the acetic acid, the concentration present in the CS/TPP nanoparticles is 0.038 mM, and as described in literature the phytotoxic effects of acetic acid on seeds are observed in concentration higher than 4 mM (Tunes et al, 2012).…”
Section: Evaluation Of Phytotoxicity Of Cs/tpp Nanoparticles and Slnmentioning
confidence: 78%
“…Although not tested separately in the present study, it is known that the CS polymer is nontoxic and for this reason has considerable potential for applications in agriculture, where it can act as a biostimulant and/or reduce abiotic stress in plants, as well as increase resistance against pathogens (Pichyangkura and Chadchawan, 2015). According to this, in recent studies of our group, different CS-based nanoparticles have been shown to not impair germination and initial growth of Phaseolus vulgaris (Pereira et al, 2017a(Pereira et al, , 2017b. Regarding the acetic acid, the concentration present in the CS/TPP nanoparticles is 0.038 mM, and as described in literature the phytotoxic effects of acetic acid on seeds are observed in concentration higher than 4 mM (Tunes et al, 2012).…”
Section: Evaluation Of Phytotoxicity Of Cs/tpp Nanoparticles and Slnmentioning
confidence: 78%
“…Zong et al (2016) in edible rape (Brassica rapa L.) found that, foliar application of chitosan promoted the plant growth and leaf chlorophyll contents. So, Pereira et al (2017) reported that, bioactivity assays using Phaseolus vulgaris showed that the alginate/chitosan (ALG/CS)-GA3 nanoparticles were most effective in increasing leaf area and the levels of chlorophylls and carotenoids.…”
Section: Discussionmentioning
confidence: 99%
“…Plant growth regulators, also known as plant hormones, such as gibberellins, auxins, abscisic acid, cytokinin and ethylene are chemical substances responsible for regulating plant growth and plant cell development. Chitosan-gibberellic acid nanoparticles exhibited a 37% and 82% increase of root development and leaf area in French bean, respectively, compared to the free hormone, gibberellic acid [38]. Apart from that, more lateral roots were formed upon supplementation of chitosan-γ-polyglutamic acid-gibberellic acid nanoparticles on French bean seedlings compared to the free hormone [39], hence highlighting the benefits of the nanoparticulate systems.…”
Section: Plant Growth Promotermentioning
confidence: 90%
“…Upon treatment, the seedlings showed an increase of leaf area, chlorophyll and carotenoids amount. [38] Chitosan-thiamine nanoparticles, 27 kDa, 85%…”
Section: Biocides Against Plant Pathogens and Pestsmentioning
confidence: 99%